Implementation and study of switched impedance boost and KY-boost converters for electric vehicle - Sreenu, Sapavath; Upendar, J.; Sirisha, B. (Institute of Advanced Engineering and Science, 2024)
A DC/DC converter based on photovoltaic (PV) grid connections is proposed here. This work focuses on the switched impedance source (S¬_ZSC) for electric vehicles. Every PV grid-connected system require step-up DC/DC converters to boost voltage range from low to high. Connecting an extra diode and a switch to the terminals of a standard quasi-impedance source DC/DC converter raises the step-up factors. In this proposed converter, this capacitor does more than just filter noise. Saturated inductors, on the other hand, can cause instability that needs not occur. In any case, the modulation index's H-bridge at its extremes is adjustable to a broader range when the circuit is used for DC-AC conversion. A larger boost factor is achieved with a shorter duty time as compared to currently available Z-source based systems. Both a buck-boost charging station and a KY-boost charging station were modeled for this investigation. PI or fuzzy logic controllers are utilized in DC-DC converters to keep the output voltage stable.